Persepsi Mahasiswa PBI terhadap Penerapan Pembelajaran Aktif Menggunakan Model Pembelajaran Kooperatif pada Mata Kuliah Drama, Prose, Poetry - Astry Fajria (Universitas Gadjah Mada, 2018)
Literary subjects are usually presented through lecturing the students in the classroom, leading them into a stage of boredom. Conversely, learning method has shifted from teacher-centered to student-centered. This way, active learning becomes necessary. The study aims to know the students’ perception on the use of active learning, especially cooperative learning, in Drama Prose Poetry subject. The research belongs to descriptive qualitative study, using closed and open questionnaires to obtain qualitative and quantitative data. The participants are 83 students taking Drama Prose Poetry subjects in the department of English Education. The results show that more than half of the participants (58 in number) agree to be more active in the classroom. Four types of cooperative learning methods are applied in the study: gallery walk, jigsaw, information gap, and drawing. Among the four activities, most students chose gallery walk as their favorite (53 in number).